Continuous production of cyclodextrins in an ultrafiltration membrane reactor, catalyzed by Cyclodextrin glycosyltransferase from Bacillus circulans DF 9R - Rodríguez Gastón, Jorgelina Andrea (2015)
Cyclodextrins (CDs) are cyclic oligosaccharides of wide industrial application, whose synthesis is catalyzed by Cyclodextrin glycosyltransferase (CGTase) from starch. Here, CDs were produced using CGTase from Bacillus circulans DF 9R in continuous process and an ultrafiltration membrane reactor. The batch process was conducted as a control. This method allowed increasing the yield from 40% to 55.6% and the productivity from 26.1 to 99.5 mg of CD per unit of enzyme. The method also allowed obtaining a high purity product. The flow rate remained at 50% of its initial value after 24 hours of process, improving the results described in the literature for starch hydrolysis processes. CGTase remained active throughout the process, which could be explained by the protective effect of the substrate and reaction products on CGTase stability. In addition, batch processes were developed using starches from different sources. We concluded that any of the starches studied could be used as substrate for CD production with similar yields and product specificity.